Unraveling the origin of stress-dependent glass transition temperature in metallic glasses. (April 2020) - Tang, Y.; Zhou, H.F.; Cao, Q.P.; Fang, Y.Z.; Wang, X.D.; Zhang, D.X.; Jiang, J.Z.
Highlights: A remarkable decrease in T g up to 250 K/GPa was obtained in metallic glasses under uniaxial tensile loading. Combing experiments and simulations, we revealed a universal picture of stress-induced T g variation in a wide range of MGs. Atomistic simulations revealed that different stress components, individually, would lead to comparable variation in T g . More importantly, an extra change of T g can be achieved through a combination of different stress components, leading to the substantial decrease in T g observed in uniaxial tension or compression. The variation in T g was linked with the stress-aided changes in local atomic configurations. Abstract: The effect of externally applied stress on glass transition temperature T g, whose underlying mechanism remains a fascinating and open question in materials science and condense-matter physics, has been explored in a range of metallic glasses (MGs) in the last decades. Recent studies have found that hydrostatic pressure leads to a slight increase in T g, while uniaxial compression causes notable decrement. However, the origin of stress-dependent T g variation is largely unknown. Here we report new results of tensile stress effect on T g in a Ni60 Nb40 (at.%) MG through in situ tensile loading and high temperature synchrotron radiation X-ray diffraction measurements. Combining our experimental data with available reports on hydrostatic pressure and uniaxial compression, a universal picture of stress-induced variation in T g of MGs under various stress states was obtained. We elucidate the physics underlying the stress-induced T g variation by decomposing the uniaxial tensile stress into a hydrostatic stress combined with two pure shear stresses, and investigating the individual contributions of the decomposed stress states on T g by atomistic simulations. Our results reveal an enhanced stress effect on T g through a combination of different stress components. The variation in T g was linked with stress-aided changes in local atomic configurations. Our theoretical predictions are shown to be in remarkable agreement with experiments, and fill the gap in the current understanding of stress-dependent T g in MGs. Graphical abstract: A summary of experimental data on stress-induced T g variation for a number of MGs. Image, graphical abstract